Prove association-law for DeltaM by (S O) pattern with definition changes
author Yasutaka Higa Sun, 01 Feb 2015 17:55:39 +0900 e6bcc7467335 6f86b55bf8b4
line wrap: on
line source
```
open import Level
open import Relation.Binary.PropositionalEquality
open ≡-Reasoning

open import basic
open import delta
open import delta.functor
open import deltaM
open import deltaM.functor
open import nat
open import laws

open Functor
open NaturalTransformation

-- sub proofs

fmap-headDeltaM-with-deltaM-eta : {l : Level} {A : Set l} {n : Nat}
{M : Set l -> Set l} {functorM : Functor M} {monadM : Monad M functorM}
(x : M A) ->  (fmap functorM ((headDeltaM {l} {A} {n} {M} {functorM} {monadM}) ∙ deltaM-eta) x) ≡ fmap functorM (eta monadM) x
fmap-headDeltaM-with-deltaM-eta {l} {A} {O} {M} {fm} {mm}    x = refl
fmap-headDeltaM-with-deltaM-eta {l} {A} {S n} {M} {fm} {mm} x  = refl

fmap-tailDeltaM-with-deltaM-eta : {l : Level} {A : Set l} {n : Nat}
{M : Set l -> Set l} {functorM : Functor M} {monadM : Monad M functorM}
(d : DeltaM M {functorM} {monadM} A (S n)) ->
deltaM-fmap ((tailDeltaM {n = n} {monadM = monadM} )  ∙ deltaM-eta) d ≡ deltaM-fmap (deltaM-eta) d
fmap-tailDeltaM-with-deltaM-eta {n = O} d = refl
fmap-tailDeltaM-with-deltaM-eta {n = S n} d = refl

-- main proofs

postulate deltaM-eta-is-nt : {l : Level} {A B : Set l} {n : Nat}
{M : Set l -> Set l} {functorM : Functor M} {monadM : Monad M functorM}
(f : A -> B) -> (x : A) ->
((deltaM-eta {l} {B} {n} {M} {functorM} {monadM} )∙ f) x ≡ deltaM-fmap f (deltaM-eta x)
{-
deltaM-eta-is-nt {l} {A} {B} {O} {M} {fm} {mm} f x   = begin
deltaM-eta {n = O} (f x)              ≡⟨ refl ⟩
deltaM (mono (eta mm (f x)))          ≡⟨ cong (\de -> deltaM (mono de)) (eta-is-nt mm f x) ⟩
deltaM (mono (fmap fm f (eta mm x)))  ≡⟨ refl ⟩
deltaM-fmap f (deltaM-eta {n = O} x)  ∎
deltaM-eta-is-nt {l} {A} {B} {S n} {M} {fm} {mm} f x = begin
deltaM-eta {n = S n} (f x) ≡⟨ refl ⟩
deltaM (delta-eta {n = S n} (eta mm (f x))) ≡⟨ refl ⟩
deltaM (delta (eta mm (f x)) (delta-eta (eta mm (f x))))
≡⟨ cong (\de -> deltaM (delta de (delta-eta de))) (eta-is-nt mm f x) ⟩
deltaM (delta (fmap fm f (eta mm x)) (delta-eta (fmap fm f (eta mm x))))
≡⟨ cong (\de ->  deltaM (delta (fmap fm f (eta mm x)) de)) (eta-is-nt delta-is-monad (fmap fm f) (eta mm x)) ⟩
deltaM (delta (fmap fm f (eta mm x)) (delta-fmap (fmap fm f) (delta-eta (eta mm x))))
≡⟨ refl ⟩
deltaM-fmap f (deltaM-eta {n = S n} x)
∎
-}

postulate  deltaM-right-unity-law : {l : Level} {A : Set l}
{M : Set l -> Set l} {functorM : Functor M} {monadM : Monad M functorM} {n : Nat}
(d : DeltaM M {functorM} {monadM} A (S n)) -> (deltaM-mu ∙ deltaM-eta) d ≡ id d
{-
deltaM-right-unity-law {l} {A} {M} {fm} {mm} {O} (deltaM (mono x)) = begin
deltaM-mu (deltaM-eta (deltaM (mono x)))             ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (eta mm (deltaM (mono x))))) ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (headDeltaM {M = M})(eta mm (deltaM (mono x))))))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (sym (eta-is-nt mm headDeltaM (deltaM (mono x)) )) ⟩
deltaM (mono (mu mm (eta mm ((headDeltaM {l} {A} {O} {M} {fm} {mm}) (deltaM (mono x)))))) ≡⟨ refl ⟩
deltaM (mono (mu mm (eta mm x))) ≡⟨ cong (\de -> deltaM (mono de)) (sym (right-unity-law mm x)) ⟩
deltaM (mono x)
∎
deltaM-right-unity-law {l} {A} {M} {fm} {mm} {S n} (deltaM (delta x d)) = begin
deltaM-mu (deltaM-eta (deltaM (delta x d)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta (eta mm (deltaM (delta x d))) (delta-eta (eta mm (deltaM (delta x d))))))
≡⟨ refl ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm (headDeltaM {monadM = mm}) (eta mm (deltaM (delta x d)))))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta mm (deltaM (delta x d)))))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono (mu mm de)))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta mm (deltaM (delta x d))))))))
(sym (eta-is-nt mm headDeltaM (deltaM (delta x d)))) ⟩
appendDeltaM (deltaM (mono (mu mm (eta mm ((headDeltaM {monadM = mm}) (deltaM (delta x d)))))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta mm (deltaM (delta x d)))))))
≡⟨ refl ⟩
appendDeltaM (deltaM (mono (mu mm (eta mm x))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta mm (deltaM (delta x d)))))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono de)) (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta mm (deltaM (delta x d))))))))
(sym (right-unity-law mm x)) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta mm (deltaM (delta x d)))))))
≡⟨ refl ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) (delta-eta (eta mm (deltaM (delta x d)))))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM de))) (sym (eta-is-nt delta-is-monad (fmap fm tailDeltaM) (eta mm (deltaM (delta x d))))) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM (delta-eta (fmap fm tailDeltaM (eta mm (deltaM (delta x d)))))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM (delta-eta de)))) (sym (eta-is-nt mm tailDeltaM (deltaM (delta x d)))) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM (delta-eta (eta mm (tailDeltaM (deltaM (delta x d)))))))
≡⟨ refl ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM (delta-eta (eta mm (deltaM d)))))
≡⟨ refl ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-eta (deltaM d)))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) de) (deltaM-right-unity-law (deltaM d)) ⟩
appendDeltaM (deltaM (mono x)) (deltaM d)
≡⟨ refl ⟩
deltaM (delta x d)
∎
-}

postulate deltaM-left-unity-law : {l : Level} {A : Set l}
{M : Set l -> Set l} {functorM : Functor M} {monadM : Monad M functorM}
{n : Nat}
(d : DeltaM M {functorM} {monadM} A (S n)) ->
(deltaM-mu ∙ (deltaM-fmap deltaM-eta)) d ≡ id d
{-
deltaM-left-unity-law {l} {A} {M} {fm} {mm} {O} (deltaM (mono x))      = begin
deltaM-mu (deltaM-fmap deltaM-eta (deltaM (mono x)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta-fmap (fmap fm deltaM-eta) (mono x)))
≡⟨ refl ⟩
deltaM-mu (deltaM (mono (fmap fm deltaM-eta x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (headDeltaM {l} {A} {O} {M}) (fmap fm deltaM-eta x))))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (sym (covariant fm deltaM-eta headDeltaM x)) ⟩
deltaM (mono (mu mm (fmap fm ((headDeltaM {l} {A} {O} {M} {fm} {mm}) ∙ deltaM-eta) x)))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (fmap-headDeltaM-with-deltaM-eta {l} {A} {O} {M} {fm} {mm} x) ⟩
deltaM (mono (mu mm (fmap fm (eta mm) x)))
≡⟨ cong (\de -> deltaM (mono de)) (left-unity-law mm x) ⟩
deltaM (mono x)
∎
deltaM-left-unity-law {l} {A} {M} {fm} {mm} {S n} (deltaM (delta x d)) = begin
deltaM-mu (deltaM-fmap deltaM-eta (deltaM (delta x d)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta-fmap (fmap fm deltaM-eta) (delta x d)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta (fmap fm deltaM-eta x) (delta-fmap (fmap fm deltaM-eta) d)))
≡⟨ refl  ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm (headDeltaM {l} {A} {S n} {M} {fm} {mm}) (fmap fm deltaM-eta x)))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono (mu mm de)))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d)))))
(sym (covariant fm deltaM-eta headDeltaM x)) ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm ((headDeltaM {l} {A} {S n} {M} {fm} {mm}) ∙ deltaM-eta) x))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono (mu mm de)))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d)))))
(fmap-headDeltaM-with-deltaM-eta {l} {A} {S n} {M} {fm} {mm} x) ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm (eta mm) x))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))

≡⟨ cong (\de -> (appendDeltaM (deltaM (mono de)) (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))))
(left-unity-law mm x) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))
≡⟨ refl ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap (tailDeltaM {n = n})(deltaM-fmap deltaM-eta (deltaM d))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) (deltaM-mu de)) (sym (covariant deltaM-is-functor deltaM-eta tailDeltaM (deltaM d))) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap ((tailDeltaM {n = n}) ∙ deltaM-eta) (deltaM d)))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) (deltaM-mu de)) (fmap-tailDeltaM-with-deltaM-eta (deltaM d)) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap deltaM-eta (deltaM d)))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) de) (deltaM-left-unity-law (deltaM d)) ⟩
appendDeltaM (deltaM (mono x)) (deltaM d)
≡⟨ refl ⟩
deltaM (delta x d)
∎

-}

fmap-headDeltaM-with-deltaM-mu : {l : Level} {A : Set l} {n : Nat}
{M : Set l -> Set l} {fm : Functor M} {mm : Monad M fm}
(x : M (DeltaM M {fm} {mm} (DeltaM M {fm} {mm} A (S n)) (S n))) ->
--                         (fmap fm headDeltaM (fmap fm deltaM-mu x)) ≡ (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x)))
--                         fmap fm (headDeltaM ∙ deltaM-mu) x ≡ fmap fm (fmap fm ((mu mm) ∙ (fmap fm headDeltaM))) x
headDeltaM (deltaM-fmap deltaM-mu (deltaM (mono x))) ≡ deltaM (mono (mu mm (fmap fm headDeltaM x)))
fmap-headDeltaM-with-deltaM-mu {l} {A} {O} {M} {fm} {mm} x = {!!}
fmap-headDeltaM-with-deltaM-mu {n = S n} x = {!!}

deltaM-mono : {l : Level} {A : Set l}
{M : Set l -> Set l} {fm : Functor M} {mm : Monad M fm}
(d : M A) -> DeltaM M {fm} {mm} A (S O)
deltaM-mono x = deltaM (mono x)

fmap-headDeltaM-with-deltaM-mono : {l : Level} {A : Set l}
{M : Set l -> Set l} {fm : Functor M} {mm : Monad M fm}
(x : M (M A)) ->
fmap fm ((headDeltaM {l} {A} {O} {M} {fm} {mm}) ∙ deltaM-mono) x ≡ x
fmap-headDeltaM-with-deltaM-mono {fm = fm} x = preserve-id fm x

deltaM-association-law : {l : Level} {A : Set l} {n : Nat}
(M : Set l -> Set l) (fm : Functor M) (mm : Monad M fm)
(d : DeltaM M {fm} {mm} (DeltaM M {fm} {mm} (DeltaM M {fm} {mm} A (S n)) (S n))  (S n)) ->
deltaM-mu (deltaM-fmap deltaM-mu d) ≡ deltaM-mu (deltaM-mu d)
deltaM-association-law {l} {A} {O} M fm mm (deltaM (mono x))    = begin
deltaM-mu (deltaM-fmap deltaM-mu (deltaM (mono x))) ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (fmap fm deltaM-mu x))) ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm headDeltaM (headDeltaM {A = DeltaM M A (S O)} {monadM = mm} (deltaM (mono (fmap fm deltaM-mu x))))))) ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x)))) ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (headDeltaM {A = A} {monadM = mm}) (fmap fm
(\d -> (deltaM (mono (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d)))))) x))))
≡⟨ cong (\de -> deltaM (mono (mu mm de)))
(sym (covariant fm (\d -> (deltaM (mono (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d))))))  headDeltaM x)) ⟩
deltaM (mono (mu mm (fmap fm ((headDeltaM {A = A} {monadM = mm}) ∙
(\d -> (deltaM (mono (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d))))))) x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (\d -> (headDeltaM {A = A} {monadM = mm} (deltaM (mono (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d))))))) x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (\d -> (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d)))) x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm ((mu mm) ∙  (((fmap fm headDeltaM)) ∙  ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm})))) x)))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (covariant fm ((fmap fm headDeltaM) ∙ (headDeltaM)) (mu mm) x )⟩
deltaM (mono (mu mm (((fmap fm (mu mm)) ∙ (fmap fm ((fmap fm headDeltaM) ∙  (headDeltaM {l} {DeltaM M A (S O)} {monadM = mm})))) x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (mu mm) ((fmap fm ((fmap fm headDeltaM) ∙ (headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}))) x))))
≡⟨ cong (\de -> deltaM (mono (mu mm (fmap fm (mu mm) de)))) (covariant fm headDeltaM (fmap fm headDeltaM) x) ⟩
deltaM (mono (mu mm (fmap fm (mu mm) (((fmap fm (fmap fm headDeltaM)) ∙ (fmap fm (headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}))) x))))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (mu mm) (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x)))))
≡⟨ cong (\de ->   deltaM (mono de)) (association-law mm (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x))) ⟩
deltaM (mono (mu mm (mu mm (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x)))))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (mu-is-nt mm headDeltaM (fmap fm headDeltaM x)) ⟩
deltaM (mono (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x)))))  ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm headDeltaM (headDeltaM {A = DeltaM M A (S O)} {monadM = mm} (deltaM (mono (mu mm (fmap fm headDeltaM x))))))))  ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (mu mm (fmap fm headDeltaM x))))  ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (mu mm (fmap fm headDeltaM (headDeltaM  {A = DeltaM M (DeltaM M A (S O)) (S O)} {monadM = mm} (deltaM (mono x)))))))  ≡⟨ refl ⟩
deltaM-mu (deltaM-mu (deltaM (mono x)))  ∎

deltaM-association-law {n = S n} M fm mm (deltaM (delta x d)) = begin
deltaM-mu (deltaM-fmap deltaM-mu (deltaM (delta x d))) ≡⟨ refl ⟩
deltaM-mu (deltaM (delta-fmap (fmap fm deltaM-mu) (delta x d))) ≡⟨ refl ⟩
deltaM-mu (deltaM (delta (fmap fm deltaM-mu x) (delta-fmap (fmap fm deltaM-mu) d))) ≡⟨ refl ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x)))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-mu) d)))) ≡⟨ {!!} ⟩

appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))) ≡⟨ {!!} ⟩
deltaM-mu (appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM x))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))≡⟨ refl ⟩
deltaM-mu (deltaM-mu (deltaM (delta x d)))
∎

deltaM-is-monad : {l : Level} {A : Set l} {n : Nat}
{M : Set l -> Set l}
(functorM : Functor M)
Monad {l} (\A -> DeltaM M {functorM} {monadM} A (S n)) (deltaM-is-functor {l} {n})
record { mu     = deltaM-mu;
eta    = deltaM-eta;
return = deltaM-eta;
bind   = deltaM-bind;
association-law = (deltaM-association-law M functorM monadM) ;
left-unity-law  = deltaM-left-unity-law;
right-unity-law = (\x -> (sym (deltaM-right-unity-law x))) ;
eta-is-nt = deltaM-eta-is-nt }

```